DAMPAK MOBILITAS PENDUDUK TERHADAP PEREKONOMIAN INDONESIA - RIRIN ANDRIANA (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2015)
This study is based on the phenomenon in public about population growth as a factor in immigration , urbanization and population mobility . Sometimes do not take into account factors moving skills and capabilities. New problems arise because of the dense population in the targeted areas . Then the local government imposed a KIPEM useful system for monitoring outside the city of Surabaya residents who work and live . Area which is the goal of population mobility in Indonesia,Java, Bali and Sulawesi . This will impact on the economic slowdown in the regions of origin of the mobility, the government made ​​a government policy that will have a major impact for disadvantaged areas which have been made the Law No. 5 2015 about the countryside that has been included budgets and the mechanism for rural development. It is expected that the PDP in 2015 may reach 5.7 % from the month of October reached 5.1 %. Researchers hope that these issues can be kept under review so as to help the government realize equitable development .